2015
DOI: 10.1039/c5ra05997f
|View full text |Cite
|
Sign up to set email alerts
|

IR 820 stabilized multifunctional polycaprolactone glycol chitosan composite nanoparticles for cancer therapy

Abstract: Photothermal therapy has gained worldwide attention for its less painful, non invasive/minimally invasive, effective thermal ablation based therapy for cancer. It has been found to be effective in the treatment of drug-resistant cancer. Currently available photothermal systems have several limitations such as a high cost, incompatibility and clearance from the physiological system. To address these issues, we have prepared multifunctional biocompatible and biodegradable cost effective IR 820 dye encapsulated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Similar shift with IR dye was previously reported by Manchanda et al, wherein they have shown three peaks around 688, 702 and 836 nm upon interaction with PEG amine NPs [28]. In our case, peak shift remains in NIR windows, giving it an additional advantage for the photothermal application [29].…”
Section: Optical and Morphological Characterizationsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar shift with IR dye was previously reported by Manchanda et al, wherein they have shown three peaks around 688, 702 and 836 nm upon interaction with PEG amine NPs [28]. In our case, peak shift remains in NIR windows, giving it an additional advantage for the photothermal application [29].…”
Section: Optical and Morphological Characterizationsupporting
confidence: 89%
“…The ease of conjugation and good stability in blood circulation make it an ideal choice for multimodal imaging and therapy [26][27][28]. In the previous studies, we have focused only on IR 820 dye based photothermal therapy for cancer treatment [29]. This can be further improved by adding immune adjuvant like GC for an immunological response.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Kumar and Srivastava successfully formulated the multifunctional, biocompatible, and biodegradable cost‐effective IR 820 dye encapsulated GC‐coated polycaprolactone nanocomposite (PCLGC–IR). The nanocomposite showed an improved performance of PTT as a theranostic because of retaining their structural integrity even after the laser treatment and showing controlled‐release profile . GC was also shown to increase the cellular uptake of these engineered nanocomposite, resulting in significant perthermic death of MDA‐MB‐231 cells.…”
Section: Cs‐based Theranosticsmentioning
confidence: 98%
“…[137][138][139] PTT is a favorable procedure since it is a less painful and noninvasive/minimally showed an improved performance of PTT as a theranostic because of retaining their structural integrity even after the laser treatment and showing controlled-release profile. 141,147 GC was also shown to increase the cellular uptake of these engineered nanocomposite, resulting in significant perthermic death of MDA-MB-231 cells.…”
Section: Photosensitizersmentioning
confidence: 99%
“…We have previously shown the significance of IR 820 and glycol chitosan (GC) in nanoformulation for effective cancer therapy [18] [19]. IR 820 stabilized PCLGC nanoparticles retain its property as a chemotherapeutic delivery agent even after laser treatment while a GC enhanced the cell death by acting as an immunostimulatory molecule.…”
Section: Introductionmentioning
confidence: 99%